Dividend policy and dividend payout: a case of industrial sector in Malaysia / Thohirah Zainun - Zainun, Thohirah (2009)
This study investigates the dividend policy and dividend payout ratios in industrial sectors of Malaysia. Specifically, the sample for this study focuses on small scope of 20 industrial companies which listed on BMSB . The estimation period for this study is from 2005 to 2009. This study aims (1) to identify the factors that determine the amount of dividends, (2) to examine the dividend payout pattern of the companies (3) to examine the relationship between EPS and DPS. Based on the findings, industrial companies in Malaysia do not have same dividend policies and the findings of previous studies that higher earning will contribute to higher dividend not significantly true for Malaysia industrial companies due to different corporate cultures and economic structures. Overall, it is important for a company to determine the factors that affects dividend payout. It is because dividend payout is one part of company’s corporate decisions which reflects the profit and shareholder’s wealth.